#Cyberbullying in the digital age: Exploring people's opinions with text mining. Issue 1 (18th October 2019) - Tahamtan, Iman; Huang, Li‐Min
ABSTRACT: This study used text mining to investigate people's insights about cyberbullying. English‐language tweets were collected and analyzed by R software. Our analysis demonstrated three major themes: (a) the major actions that needed to be taken into consideration (e.g. guiding parents and teachers to cyberbullying prevention, funding schools to cope with cyberbullying), (b) certain events that were important to people (e.g. the Michigan cyberbullying law), and (c) people's major concerns in this regard (e.g. mental health issues among students). Parents and teachers have an important role in educating, informing, warning, preventing, and protecting against cyberbullying behaviors. The frequency of negative sentiments was almost 2.45 times more than positive sentiments.